Opportunities and Challenges in Developing Nuclear Security in Africa - James Larkin Mfr (International Journal of Nuclear Security, 2016)
Those involved in nuclear security recognize that regions of significant instability in Africa have an impact on the safety and security of the continent's nuclear material and un-enriched uranium; however, some countries outside of continental Africa have taken counterproductive approaches to this issue. Despite challenges, the nuclear security community continues to develop and apply appropriate levels of nuclear security where needed. The community also takes every opportunity to make significant contributions to the global discourse on nuclear security culture.
Keywords: nuclear security culture; cultural beliefs; need; propaganda of the deed